Quo Vadis Urgensi Pembentukan Otoritas Independen atas Kesepakatan Transfer Data Pribadi Warga Indonesia ke Amerika Serikat - Muhammad Charles Nur Oktawijaya (Universitas Sultan Ageng Tirtayasa, 2026)
The rapid development of the digital economy has accelerated cross-border personal data transfers, creating challenges related to data protection and state sovereignty. In Indonesia, Law Number 27 of 2022 concerning Personal Data Protection has established a legal framework to safeguard privacy rights, including the regulation of international data transfers through the principle of adequacy. This study aims to analyze the urgency of establishing an independent supervisory body in overseeing cross-border personal data transfers and ensuring compliance with constitutional rights protection. The research employs a normative legal method using statute, conceptual, comparative, and philosophical approaches. The findings reveal that although the adequacy principle has been regulated under Article 56 of the Personal Data Protection Law, its implementation remains ineffective due to the absence of a clear supervisory mechanism and institutional authority to evaluate the level of protection in recipient countries. This condition creates regulatory gaps, weakens legal enforcement, and increases the risk of personal data misuse. Therefore, the establishment of an independent supervisory authority with integrated oversight, regulatory, and enforcement functions is essential to strengthen accountability, maintain data sovereignty, and ensure effective protection of personal data in the digital era.